Invariant features of multijoint control strategies used by gymnasts during landings performed in Olympic competition - McNitt-Gray, J. L.; Munkacsy, B. A.; Costa, K.; Mathiyakom, D.; Eagle, J.; Ryan, M. M. (1998)
As expected, the total body center of mass (TBCM) vertical velocities at contact were greater for the HB landings than for the PB landings. Of the twenty landings performed, only one was successful (no steps or hops), eight were over rotated (step or hop backward) and eleven were under rotated (step or hop forward). The success rate over and under rotated PB and HB landings in this study are in line with those observed during the 1992 Olympic competition (McNitt-Gray, 1992). Over rotated PB landings were characterized by more vertical line between the TBCM and ankle at contact (65-78 degrees relative to the horizontal), whereas, under rotated PB landings were characterized by a more horizontal line (61-66 degrees relative to the horizontal). Unsuccessful HB landings demonstrated a similar but less definitive trend (over rotated: 79,86 degrees; successful: 73 degrees; under rotated: 69-80 degrees relative to the horizontal). These results suggest landing success on parallel bars may be directly related to the angular position of the TBCM at contact. All subjects prepared for contact by retracting their legs prior to contact (leg velocity falling at a slower rated than the TBCM) during both the PB and HB landings, as found by Munkasy et al.(1992). All subjects initiated contact with a greater hip angle during the HB landings than during the PB landings (range: 23 to 35 degree increase relative to PB hip angle at contact). No major differences in knee angle at contact were observed between PB and HB landings. These results suggest gymnasts may be compensating for greater TBCM vertical velocities at contact by increasing their hip angle at contact. A relationship between hip angle and TBCM vertical velocity at contact, however was not observed when female gymnasts performed drop landings from progressively higher heights. This difference in results between studies may be due to the magnitude of hip extension at contact (hip angles at contact in this study averaged 30 degrees less than those observed for female gymnasts during drop landings onto mats from 1.82 m, McNitt-Gray et al., 1993). After contact, knee angle-hip angle relationships observed within subject for the PB and HB landings revealed consistent coordination patterns (slope) between the knee and hip for nine of the ten subjects. The remaining subject demonstrated consistent coordination patterns between the knee and hip angular velocities. These data indicate control of knee and hip flexion after contact may be subject specific and independent of landing success or TBCM velocity at contact. Invariant knee angle-hip angle relationships observed after contact lend support for tendonous like action by biarticular muscles as a potential means of coordinating adjacent joints during ballistic multijoint movements. Adjacent joint kinetics and muscle activation of biarticular muscles observed during back salto landings performed by male collegiate gymnasts (McNitt-Gray, et al., 1993) also suggest biarticular muscles may play a positive role in both coordinating and distributing load during multijoint movements involving impact.